Pengaruh Keseimbangan Kehidupan Kerja terhadap Kinerja Auditor dengan Stres Kerja Sebagai Variabel Mediasi - Wahid Rakhmanto; Titik Rosnani (VISA: Journal of Vision and Ideas, 2024)
This research was conducted to determine and analyze the influence of work-life balance through the mediating variable work stress on the performance of BPK auditors representing West Kalimantan Province. The research respondents were 30 auditors who held the positions of first expert examiner and junior expert examiner. Data collection was carried out through an online questionnaire by providing an assessment of work-life balance indicators, testing work stress as a mediation and measuring its impact on the performance of BPK auditors. The data obtained was then analyzed using SmartPLS version 4 software. The results showed that work-life balance had no significant effect on auditor performance, work-life balance had a significant effect on auditor work stress, work stress had a significant effect on auditor performance and work-life balance had a significant effect on auditor performance through the mediating role of work stress.